The Arc of the Horn Part II: Sacral powers of the ibex on the seals of Persepolis - Root , Margaret Cool (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
This is Part II of a sequence of articles on the roles and meanings of the ibex (wild mountain goat) in ancient Iran as viewed through the visual record. Central to our discussions is the significance in this cultural setting of the male ibex as the unique source of a special curative agent. Perhaps due to the particular lifeways of the ibex, the composition of its digestive concretions (bezoar stones) seemed to render them magically effective against venomous snakebite. Part I explores features of the ibex in nature and in the man-land-animal world of pre-Achaemenid Iran, documented most notably through early a small core of available excavated glyptic representations. Here in Part II, we explore this theme from the vantage point of the Achaemenid Persian imperial heartland capital, Persepolis. The primary material for Part II emerges from analysis of a large glyptic dataset from the excavated administrative records we call the Persepolis Fortification Archive. This evidence demonstrates how the roles and meanings of the ibex in Persepolis both developed from earlier traditions of Iran and blossomed into fresh formulations resonant with ideals of a righteous sacral sphere related to Iranian cult and Achaemenid royal ideology.